2001
DOI: 10.1076/opep.8.2.145.4169
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of trachoma in the absence of antibiotic treatment: Evidence from a population-based survey in Malawi

Abstract: Since 1983 there has been no mass antibiotic treatment programme in the district and little change in socioeconomic status. However, compared to the 1983 findings, active trachoma has been reduced by over 50% (p < 0.001) and trachomatous trichiasis by over 80%. In the 16-year interim (especially in the past 7 years) health, water and hygiene programmes were initiated and we hypothesize that the reduction in active disease is likely due to these changes. Our findings suggest that sustained reductions in active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 8 publications
(10 reference statements)
2
43
0
Order By: Relevance
“…Declines in trachoma have been observed in other African countries with improvements in development 16 17. Household sanitation is lacking in the seven LGAs targeted for AFE interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Declines in trachoma have been observed in other African countries with improvements in development 16 17. Household sanitation is lacking in the seven LGAs targeted for AFE interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Because there had been only a modest program of antibiotic administration in 1959-1961, the authors attributed the decline to trends independent of the active trachoma program [18]. Similarly, another recent report found that the average prevalence of active trachoma among children in a district in Malawi had decreased from 37% to 14% between 1983 and 1999 in the absence of organized distribution of antibiotics [19].…”
mentioning
confidence: 94%
“…[40][41][42] Trachoma has also been shown to disappear where water has bed d come available, even in the absence of an antibioticdbased control programme. 43,44 Provision of water sources is a compod d nent of a few national programmes, such as that in Morocco, but the perceived high cost makes it unattainable for most. Improving access to safe drinking water is included in Millennium Development Goal 7, 45 and national programmes are using this goal to ensure that water prod d vision is prioritized for communities where trachoma is endemic.…”
Section: Facial Cleanliness and Envi--ronmental Improvementmentioning
confidence: 99%